Circulating miRNAs in genitourinary cancer: pioneering advances in early detection and diagnosis - Annunziata Gaetana Cicatiello; Michele Musone; Silvestro Imperatore; Carlo Giulioni; Roberto La Rocca; Angelo Cafarelli; Francesco Del Giudice; Monica Dentice; Felice Crocetto (The Journal of Liquid Biopsy)
MicroRNAs (miRNAs) are noncoding, single-stranded RNAs molecules modulating gene expression thanks to their ability to bind mRNAs. Indeed, they regulate key processes for the proper functioning of the organism and affect the course of human pathologies. Altered expression of individual miRNAs has been shown in most human cancers, endowed with oncogenic or suppressor potential. Additionally, miRNAs have shown a promising potential as cancer markers. Not only miRNAs are present in various body fluids, such as serum and plasma, they also have high biological stability of miRNAs that in turn facilitates their detection. For these reasons, the use of miRNAs detection as non-invasive prognostic and predictive biomarkers in cancer provides new perspectives and strategies for personalized medicine and cancer therapy.This review summarizes the current knowledge supporting the utility of miRNAs as novel early diagnostic and prognostic tool, with a special focus on the effectiveness of miRNAs of the liquid biopsies in the diagnosis of urogenital cancers. In conclusion, we rightly state that circulating miRNAs and therefore liquid biopsy have the potential to revolutionize the diagnosis, monitoring and even treatment of urological tumors, entering clinical practice as a more accurate, less invasive and more suitable diagnostic tool for patient follow-up compared to current methodologies. With the progress of scientific research and the implementation of advanced technologies that also exploit artificial intelligence, the future of oncological diagnosis, especially for urological tumors, could be increasingly oriented towards less invasive approaches and based on precision medicine, tailored for the specific patient.